grammatical issues in Arabic proverbs (Journal of the College of Basic Education, 2022)
The Arabs took great care of proverbs, and this care was reflected in their many books.The authors used several methods in their writings, and many of their books became famous, including (Collection of Proverbs).by Al-Maidani (d. 518 AH) and (Al-Muqtissah fi Al-Athbulah) by Al-Zamakhshari (d. 538 AH), and many others“Because the proverbs are chosen, dictated by the human experience, and passed on by the tongues, and they included experience and the wordand the sermon.” (1) Proverbs have the power to survive, because they are the juice of human experiences full of life.